Illumina MiSeq sequencing reveals microbial community in HA process for dyeing wastewater treatment fed with different co-substrates. (June 2018) - Xie, Xuehui; Liu, Na; Ping, Jing; Zhang, Qingyun; Zheng, Xiulin; Liu, Jianshe
Abstract: In present study, a hydrolysis acidification (HA) reactor was used for simulated dyeing wastewater treatment. Co-substrates included starch, glucose, sucrose, yeast extract (YE) and peptone were fed sequentially into the HA reactor to enhance the HA process effects. The performance of the HA reactor and the microbial community structure in HA process were investigated under different co-substrates conditions. Results showed that different co-substrates had different influences on the performance of HA reactor. The highest decolorization (50.64%) and COD removal rate (60.73%) of the HA reactor were obtained when sucrose was as the co-substrate. And it found that carbon co-substrates starch, glucose and sucrose exhibited better decolorization and higher COD removal efficiency of the HA reactor than the nitrogen co-substrates YE and peptone. Microbial community structure in the HA process was analyzed by Illumina MiSeq sequencing. Results revealed different co-substrates had different influences on the community structure and microbial diversity in HA process. It was considered that sucrose could enrich the species such as Raoultella, Desulfovibrio, Tolumonas, Clostridium, which might be capable of degrading the dyes. Sucrose was considered to be the best co-substrate of enhancing the HA reactor's performance in this study. This work would provide deep insight into the influence of many different co-substrates on HA reactor performance and microbial communities in HA process. Highlights: Effects of different co-substrates on the performance of HA process were studied. Effects of co-substrates on microbial community in HA process were studied. Sucrose was considered the best co-substrate to enhance HA reactor's performance. Microbial community varied largely under different co-substrates conditions. Species that might be responsible for dye degradation were enriched by sucrose.